Principles and practice of agricultural analysis. Volume 3 (of 3), Agricultural products - Wiley, Harvey Washington, 1844-1930 (Salt Lake City, UT : Project Gutenberg, 2025)
"Principles and Practice of Agricultural Analysis. Volume 3" by Harvey W. Wiley is a scientific publication written in the late 19th century. This work serves as a manual for the examination of soils, fertilizers, and agricultural products, focusing specifically on methods for analyzing agricultural products. The book is intended for analysts, teachers, and students of agricultural chemistry, providing them with comprehensive guidance on various analytical techniques. At the start of this volume, the author outlines the different approaches to agricultural analysis, emphasizing the importance of correctly preparing samples and selecting appropriate methods based on the study's objectives. Wiley introduces the principles of sampling, drying, incineration, and extraction processes, laying a foundation for the detailed discussions that will follow in the subsequent chapters. He also stresses the necessity of relying on the judgment and experience of the chemist in selecting methods, as opposed to rigidly adhering to prescribed techniques, reflecting a broader educational goal for readers who are already versed in analytical chemistry. (This is an automatically generated summary.)
Release date is 2025-02-16
Peter Becker and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Soils; Agricultural chemistry; Fertilizers; Farm produce